2023
DOI: 10.1044/2023_jslhr-22-00545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Healthy Aging and Gender on the Electrophysiological Correlates of Semantic Sentence Comprehension: The Development of Dutch Normative Data

Abstract: Purpose: The clinical use of event-related potentials in patients with language disorders is increasingly acknowledged. For this purpose, normative data should be available. Within this context, healthy aging and gender effects on the electrophysiological correlates of semantic sentence comprehension were investigated. Method: One hundred and ten healthy subjects (55 men and 55 women), divided among three age groups (young, middle aged, and elderly), pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 87 publications
1
6
0
1
Order By: Relevance
“…In this context, effects of healthy ageing and gender on the elicited ERPs/ERFs should also be taken into account when interpreting the results of patients. Therefore, the availability of normative data for men and women from different age groups is beneficial (Aerts et al, 2013; Cocquyt et al, 2022; Cocquyt et al, in press; Dorme et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, effects of healthy ageing and gender on the elicited ERPs/ERFs should also be taken into account when interpreting the results of patients. Therefore, the availability of normative data for men and women from different age groups is beneficial (Aerts et al, 2013; Cocquyt et al, 2022; Cocquyt et al, in press; Dorme et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“… Lexical decision task (Holcomb & Neville, 1990) Categorical/associative word priming task (Cocquyt et al, 2022) Semantic sentence verification task (Cocquyt et al, in press) Presented in the auditory or visual modality …”
Section: Introductionmentioning
confidence: 99%
“…In the paper of Cocquyt et al. ( 2023 ), the authors found that the latency of the N400 effect, i.e. the difference between the incorrect and correct evoked responses between 0.3 s and 0.5 s after stimulus onset, was significantly delayed in elderly subjects (ages 60) compared to both young (ages 20–39) and middle-aged subjects (ages 40–59).…”
Section: Methodsmentioning
confidence: 99%
“…For the second experimental dataset involving the N400 component elicited using a semantic sentence congruity task (SSCT), the dataset recorded by Cocquyt et al. ( 2023 ) was used. Briefly, 120 sentences, half of which were semantically correct while the other half contained a semantic violation at the end, were visually presented to 110 individuals.…”
Section: Methodsmentioning
confidence: 99%
“…fanden zudem einen Einfluss des Alters auf den N400-Effekt, der für die CI-Gruppe und die Kontrollgruppe gleichermaßen galt: Der N400-Effekt war für ältere Probanden geringer ausgeprägt als für jüngere Probanden. Dies repliziert Befunde aus der Literatur[22,23,24]. Die Ursache dieses Effekts ist noch ungeklärt.…”
unclassified